Strategi Guru dalam Mengatasi Kesulitan Siswa dalam Menulis Bahasa Arab - Juliadin Al-Ghifari; Syaiful Anam (STIKes Ibnu Sina Ajibarang, 2025)
Arabic writing is one of the important skills in learning Arabic, but many students have difficulty in mastering it. This study aims to identify strategies used by teachers in overcoming students' difficulties in writing Arabic. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the main difficulties experienced by students include limited vocabulary, understanding of grammatical structures (nahwu and sharaf), and lack of directed writing exercises. To overcome these problems, teachers apply several strategies, including: the use of interactive learning media, a contextual approach in teaching vocabulary, gradual structured writing exercises, and providing regular feedback. In addition, teachers also encourage students to read simple Arabic texts as an effort to improve their understanding of sentence structures and enrich their vocabulary. These strategies have been proven to help improve students' writing skills gradually. This study concludes that the active role of teachers, creativity in learning, and an approach that suits students' needs are very important in overcoming difficulties in writing Arabic among students.